FUNCTIONAL OUTCOME OF PROXIMAL HUMERAL FRACTURES TREATED WITH PHILOS PLATE IN ADULTS - Aliuddin, Akram Muhammad; Idrees, Zaki; Zamir, Mehroze; Najjad, Muhammad Kazim Rahim; Shah, Syed Amir Ali (Journal of Ayub Medical College Abbottabad, 2016)
Background: Proximal humeral fractures account for 4-5% of all fractures. Most fractures are minimally displaced and can be managed non-operatively in adults. Displaced and unstable fractures are difficult to manage and should be treated to achieve painless shoulder and full function. Our aim was to evaluate the functional outcome of proximal humerus fractures (Neers classification 2 part, 3 part and 4 part) treated with PHILOS (Proximal humeral internal locking system). Methods: We retrospectively reviewed 22 patients who had proximal humerus fractures treated with PHILOS plate from Jan 2012 to June 2013 conducted at Orthopaedic Department Liaquat National Hospital. Clinical outcome was measured using DASH (disability of arm, shoulder and hand) Score System. Radiological union was assessed by serial X rays. Result. Two patients were lost to follow up. Mean age was 40 years (20-70). Mean follow up was 6 months. 4 patients had two-part fracture, 10 patients had three-part and 6 patients had four-part fracture. Radiological union was achieved in average 8.31 weeks (±1.37SD). Average DASH score in young patients was 15.14 (±1.91SD) and in elderly was 31.66 (±4.08SD). One case of implant failure was noted. Better results in younger patients were achieved as compared to elderly proved by DASH score. Conclusion: Increase in number of fracture parts and delay in treatment did not affect the outcome. Our study concluded that this implant provides stable fixation in younger patients with good quality bone sufficient to allow mobilization. Keywords: Proximal Humeral Fractures, PHILOS, DASH, functional outcome, adults, humerus, adults